KARAKTERISASI MORFOLOGI DAN FISIOLOGI MIKROB PELARUT FOSFAT DAN MIKROB PENAMBAT N2 (AZOTOBACTER) DARI RHIZOSFER TANAMAN PADI DAN TANAH HUTAN CIFOR DRAMAGA BOGOR - Maatoke, Cornelia Dolfina; Dewani, Zahriska; Suciati, Fuzi (Universitas Lancang Kuning, 2024)
This study aims to determine the morphological and physiological properties of Phosphate Solubilizing Microbes (MPF) and Azotobacter. The method used was to test morphological properties using gram staining and physiological properties tests using biochemical tests based on cell activity by looking at the interaction of bacterial metabolism with the test reagent media. Data analysis examined the reaction to the isolated morphological and physiological test media. The results showed that based on the morphological observations of the MPF, the colonies showed a slightly milky white color, round, convex, slimy shape, 1-2 mm in diameter and flattened, and Gram-positive. Azotobacter shows the characteristics of transparent color, convex, flat edges, slightly slimy, an average diameter of 1 mm, and is Gram-negative; whereas based on the results of physiological test observations for catalase and oxidation tests, the characteristic of MPF and Azotobacter, each showed a positive (+) effect, as seen from the formation of bubbles in the test results. Tests for motility and O2 requirements show that both bacteria are motile, mobile and aerobic or require oxygen for growth. The observations of resistance in the pH range showed that Azotobacter was more resistant to extreme acid-base pH with a pH range of 3-9, while MPF could only survive in a pH range of 5-9. Tests of glucose and sucrose fermentation showed that MPF did not form gas bubbles (-) and no color change(-). At the same time, Azotobacter showed the formation of gas bubbles (+) but no color change (-).